Linguodidactic Principles of Organizing the Process of Teaching Foreign Languages Under Conditions of European Integration (Journal of Pedagogical Inventions and Practices, 2023)
The purpose of the article is issuing the question of foreign language teaching within eurointegration context, in particular development of students’ foreign integrative skills. Based on the given lingvodydactic principles, the authors prove the possibility of foreign language study to obtain the communicative status.